RANCANG BANGUN SISTEM KONTROL WATER DANCING BERBASIS ARDUINO DAN ANDROID - Furqan a’la maududy; Munzir Umran; Safwan; Ichsan; Dien Taufan (Politeknik Aceh, 2019)
Generally, in Banda Aceh there are several entertainment venues that provide water dancing which are still monotonous and unvaried. This situation is caused by the absence of new innovations that are displayed to be enjoyed. To deal with, this final project created an this application can provide water dancing with varied patterns. This tool can be controlled via android. Furthermore, it uses Arduino Mega, DC Motor, L293D motor driver, Android.